2022
DOI: 10.21608/svuijas.2021.106875.1154
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and genetical identification of some vermicompost beneficial associated bacteria

Abstract: In the present work, isolation and identification of some plant beneficial bacteria of vermicompost were conducted. A total of ten bacterial isolates were selected and characterized morphologically and biochemically. Molecular characterization of the bacterial isolates using 16S rRNA gene sequence analysis and phylogenic tree were conducted. According to the percentages of homology of 16S rRNA sequence with the closest NCBI strain, all of the ten bacterial isolates were belonged to six species (B. subtilis, B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…cucumerinum (FOC) in cucumber. Soltan et al 37 found that the ten bacterial isolates obtained from vermicompost had an in vitro antagonistic effect against Fusarium solani , Fusarium spp., M. phasolenia and Rhizoctonia solani .…”
Section: Discussionmentioning
confidence: 99%
“…cucumerinum (FOC) in cucumber. Soltan et al 37 found that the ten bacterial isolates obtained from vermicompost had an in vitro antagonistic effect against Fusarium solani , Fusarium spp., M. phasolenia and Rhizoctonia solani .…”
Section: Discussionmentioning
confidence: 99%